2014
DOI: 10.1021/jp4125167
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Electronic Properties of Transition Metal-Containing Ionic Liquids: Insights from Ion Pairs

Abstract: Transition metal-containing ionic liquids (TM-ILs) have attracted a great deal of attention in recent years, due to their unique physical and chemical properties. In this work, several representative TM-ILs, such as the cations consisting of silver(I) center coordinated by two n-alkylimidazole ligands ([(C(n)(im))Ag(mim)](+)) and the anions involving mercury(II) (HgCl3(-)), zinc(II) (ZnCl3(-)), and rhenium(VII) (ReO4(-)), were investigated using density functional theory calculations. First, the structural and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…35 Very recently, we have successfully utilized the B3LYP/aug-cc-pVDZ(-PP) method to study the structures and electronic properties of halogenated ILs and transition metal-containing ILs. 36,37 All the optimized structures were confirmed to be minima on the potential energy surface via vibrational frequency analysis at the same level of theory. All of these computations were carried out with the help of Gaussian 09 suite of programs.…”
Section: Theoretical Methodsmentioning
confidence: 83%
“…35 Very recently, we have successfully utilized the B3LYP/aug-cc-pVDZ(-PP) method to study the structures and electronic properties of halogenated ILs and transition metal-containing ILs. 36,37 All the optimized structures were confirmed to be minima on the potential energy surface via vibrational frequency analysis at the same level of theory. All of these computations were carried out with the help of Gaussian 09 suite of programs.…”
Section: Theoretical Methodsmentioning
confidence: 83%
“…Their research shows that some obvious changes in electrostatic potential distribution were observed after introducing metal salts into the ILs. To be more specific, cation–anion interactions in these metal‐containing ILs are weaker than in pure ILs, according to the results of the electrostatic potential distribution analysis . We reasonably assume that ILs with weakened cation–anion interactions have higher reactivity.…”
Section: Resultsmentioning
confidence: 87%
“…After dissolution of metal salt in IL, characteristics of both the IL and the metal cation essentially change . Lu and co‐workers studied structures and electronic properties of metal‐containing ILs using electrostatic potential distribution analysis . Their research shows that some obvious changes in electrostatic potential distribution were observed after introducing metal salts into the ILs.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to only about 600 molecular solvents currently used, approximately 10 18 ILs can be generated from possible combinations of various cations and anions [27]. As a result, ionic liquids are considered designer solvents because properties like; solubility, polarity, melting point, viscosity, and density, can be tailored to meet specific applications by varying the cation or anion [22,24,28]. Various studies have worked on understanding the structure-property relationship of these solvents in order to elucidate the dominant forces that impact their properties, enabling them to influence chemical reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have worked on understanding the structure-property relationship of these solvents in order to elucidate the dominant forces that impact their properties, enabling them to influence chemical reactivity. For instance, studies on the geometric and energetic properties on imidazolium cation-containing ILs have revealed that the anion prefers to reside over the imidazole ring forming a hydrogen bond with the acidic C 2 -H group [28]. Other non-covalent interactions like coulombic forces [29], van der Waals interactions [27] and π-π stacking [25] have been found to be key and dominate the behavior of ILs hence significantly influence their properties.…”
Section: Introductionmentioning
confidence: 99%